The usefulness of Duplex Doppler ultrasound in the angiological and dermatological diagnosis of patients with blue toe syndrome - Pawlaczyk, Katarzyna; Gabriel, Marcin; Strzelecka-Wêklar, Daria A.; Krasiński, Zbigniew; Stanisic, Michal; Gabriel, Zofia; Dzieciuchowicz, Łukasz; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Peripheral microembolism is one of the most frequent causes of acute limb ischemia. In order to effectively prevent relapses it is essential to localize and eliminate the source of embolism. Aim : To evaluate the role of Duplex Doppler ultrasound examination in identifying the causes of blue toe syndrome (BTS). Material and methods : The group of 165 patients with clinical symptoms of BTS on their upper limbs (n = 16) and lower limbs (n = 149) was investigated. They all underwent Duplex Doppler ultrasound of the major arteries of the extremities, where ischemic changes occurred. Results : Morphological and functional changes which might be potential sources of microembolism were identified in 146 patients. These changes included significant short-length stenoses or unstable atherosclerotic plaque (n = 73), true aneurysms (n = 42) and pseudoaneurysms (n = 17). In 11 cases, pathology of vascular prostheses in the form of anastomotic aneurysms, infection and residual thrombi after fibrinolysis was detected. In all cases, Duplex diagnosis was confirmed by other imaging and intraoperative tests. Conclusions : Duplex Doppler ultrasound of the arteries in the affected limb with a full length view should be the first-line examination in diagnosing patients with BTS. In the absence of hemodynamic blood flow disturbances in the major arteries in patients with symptoms of BTS, it is advisable to start haematological tests to identify/exclude congenital or acquired thrombophilia.